1988
DOI: 10.1063/1.340708
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic structure of UCu2Si2 and U(Cu0.75Mn0.25)2Si2

Abstract: The replacement of Cu by Mn in UCu2Si2 causes surprisingly large increases in both the Curie temperature and the coercivity of this ferromagnetic material. We have performed neutron powder diffraction experiments on a series of U(Cu,Mn)2Si2 alloys and found that UCu2Si2 is a simple ferromagnet with a magnetic moment of 2.0(1)μB on the U atoms pointing along the crystallographic c axis of the tetragonal unit cell. The alloy U(Cu0.75Mn0.25)2Si2 is also a ferromagnet with moments on both U and Mn pointing in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Their neutron-diffraction study showed ferromagnetic ordering below T C = 103(3) K and down to 4.2 K, with uranium magnetic moments along the c axis. They correlated their neutron-diffraction observations with their magnetization measurements in an applied field of 1 T, which also indicated ferromagnetic ordering below a comparable temperature of 107 K. Shortly afterwards Hiebl and Rogl [31] studied an annealed polycrystalline sample of UCu 2 Si 2 by magnetization measurements (shown for applied fields of 1.00 and 1.18 T) and found only ferromagnetic ordering below T C = 105 K and down to 1.8 K. At the same time Giorgi et al [32] studied a polycrystalline sample (with no annealing details) of UCu 2 Si 2 by neutron-diffraction and magnetization measurements and confirmed its ordering as a simple ferromagnet. Later on Hiebl et al [33] studied an annealed stoichiometric polycrystalline sample of UCu 2 Si 2 , which was well characterized, by magnetization measurements (shown for an applied field of 0.1 T) and found only ferromagnetic ordering below T C = 105(5) K and down to 2 K. They emphasized the role of movements of the narrow domain walls in the magnetization processes (as mentioned above, generally in section 2 and for UCu 2 Ge 2 in section 3).…”
Section: The Case Of Ucu 2 Simentioning
confidence: 82%
“…Their neutron-diffraction study showed ferromagnetic ordering below T C = 103(3) K and down to 4.2 K, with uranium magnetic moments along the c axis. They correlated their neutron-diffraction observations with their magnetization measurements in an applied field of 1 T, which also indicated ferromagnetic ordering below a comparable temperature of 107 K. Shortly afterwards Hiebl and Rogl [31] studied an annealed polycrystalline sample of UCu 2 Si 2 by magnetization measurements (shown for applied fields of 1.00 and 1.18 T) and found only ferromagnetic ordering below T C = 105 K and down to 1.8 K. At the same time Giorgi et al [32] studied a polycrystalline sample (with no annealing details) of UCu 2 Si 2 by neutron-diffraction and magnetization measurements and confirmed its ordering as a simple ferromagnet. Later on Hiebl et al [33] studied an annealed stoichiometric polycrystalline sample of UCu 2 Si 2 , which was well characterized, by magnetization measurements (shown for an applied field of 0.1 T) and found only ferromagnetic ordering below T C = 105(5) K and down to 2 K. They emphasized the role of movements of the narrow domain walls in the magnetization processes (as mentioned above, generally in section 2 and for UCu 2 Ge 2 in section 3).…”
Section: The Case Of Ucu 2 Simentioning
confidence: 82%